Translocation of introduced reindeer from Hagemeister Island, Alaska - Stimmelmayr, R.; Renecker, L. A. (Rangifer, 1998)
In 1992 and 1993, 411 live reindeer were shipped by air from Hagemeister Island to the Anchorage area, Alaska. Reindeer were either rounded up by helicopter and then corralled or captured by net-gun fired from a helicopter. Outcome of both capture events showed that helicopter corralling of reindeer was more successful than catching them with a net-gun and that post-rut rounding up was more successful than rounding up during the rut itself.